2011
DOI: 10.1002/jnr.22678
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of cyclin‐dependent kinase 5 but not of glycogen synthase kinase 3‐β prevents neurite retraction and tau hyperphosphorylation caused by secretable products of human T‐cell leukemia virus type I‐infected lymphocytes

Abstract: Human T-cell leukemia virus type I (HTLV-I)-associated myelopathy/tropical spastic paraparesis (HAM/TSP) is a neurodegenerative disease characterized by selective loss of axons and myelin in the corticospinal tracts. This central axonopathy may originate from the impairment of anterograde axoplasmic transport. Previous work showed tau hyperphosphorylation at T181 in cerebrospinal fluid of HAM/TSP patients. Similar hyperphosphorylation occurs in SH-SY5Y cells incubated with supernatant from MT-2 cells (HTLV-I-i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
26
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 48 publications
(62 reference statements)
0
26
0
1
Order By: Relevance
“…A retraction model with differentiated neuroblastoma cells (SH-SY5Y cells) gave us similar effects with culture media from both MT2 or PBMCs from HAM/TSP patients confirming the validity of using this cell line as well. 19,23 In conclusion, the interaction between secreted Tax and soluble SEMA-4D from HTLV-1-infected human lymphocytes led us to suggest a leading role for Tax in the SEMA-4D-Plexin 1B signaling pathway. The chemoattractant effect of sSEMA-4D on infected PBMCs exhibiting CRMP-2 pSer 522 implies a higher CNS infiltration of infected T cells, increasing both the occurrence of SEMA-4D T cells and sSEMA-4D levels in CSF.…”
mentioning
confidence: 88%
See 1 more Smart Citation
“…A retraction model with differentiated neuroblastoma cells (SH-SY5Y cells) gave us similar effects with culture media from both MT2 or PBMCs from HAM/TSP patients confirming the validity of using this cell line as well. 19,23 In conclusion, the interaction between secreted Tax and soluble SEMA-4D from HTLV-1-infected human lymphocytes led us to suggest a leading role for Tax in the SEMA-4D-Plexin 1B signaling pathway. The chemoattractant effect of sSEMA-4D on infected PBMCs exhibiting CRMP-2 pSer 522 implies a higher CNS infiltration of infected T cells, increasing both the occurrence of SEMA-4D T cells and sSEMA-4D levels in CSF.…”
mentioning
confidence: 88%
“…22 Our group has reported that Tax secreted from an HTLV-1-infected human T cell line (MT2) produced retraction in neuroblastoma cells, SH-SY5Y. 23 This effect could be mediated by Tax as well as by other proteins released from HTLV-1-infected lymphocytes such as a proteolytically shed form of Semaphorin 4D, SEMA-4D (150-kDa transmembrane glycoprotein), called soluble Semaphorin 4D, sSEMA-4D. This soluble semaphorin is a bioactive soluble form of 120-kDa that upon binding to its neuronal receptor Plexin B1 induces growth cone collapse.…”
Section: Introductionmentioning
confidence: 99%
“…Valenzuela and collaborators recently found that cyclindependent kinase (Cdk)5 prevents Tau hyper-phosphorylation caused by HTLV-1-infected cell secretions [31] , but further studies are needed to understand the relevance of those modifications.…”
Section: Cerebrospinal Fluid In Ham/tspmentioning
confidence: 99%
“…18 BDNF was removed from the culture medium and replaced by a mixture of DMEM-F12 Ham without fetal bovine serum 4 h previous to the addition of culture medium of PBMCs. In all experiments DMEM-F12 was replaced by PBMC culture medium, being differentiated in SH-SY5Y cells incubated up to 2 h with (1) culture medium of PBMCs from an HAM/TSP patient, (2) culture medium of PBMCs from an HAM/TSP patient with 10 ll/ml of either Tax antibody (HTLV-1 Tax Hyb 168A51-2) or a same isotype irrelevant antibody (anti-Gizzerosine), and (3) with culture medium of PBMCs from a healthy subject.…”
Section: Neurite Retraction Studies On Sh-sy5y Cellsmentioning
confidence: 99%
“…17 Incubation of human SH-SY5Y neuroblastoma cells with culture medium of MT-2 cells (an HTLV-1-infected cell line that secretes viral Tax protein) produces neurite retraction and an increase in Tau phosphorylation at T181. 18 Tax, a 40-kDa protein, undergoes posttranslational modifications such as phosphorylation, ubiquitination, SUMOylation, and acetylation. 15,16,[19][20][21][22][23][24] Phosphorylation is critical for Tax transactivation via both the ATF/CREB and NF-jB pathways.…”
mentioning
confidence: 99%